MIGRASI ZIRKONIUM DAN HAFNIUM PADA TUMPUKAN RESIN ANION DALAM RANGKA SIMULASI PEMISAHANNYA DENGAN KROMATOGRAFI ANULAR - , GDE PANDHE WISNU SUYANTARA, Prof. Ir. Wahyudi Budi Sediawan, S.U., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Zirconium is non-corrosive material and has high melting point. Due to its low neutron capture cross section, zirconium can be used as cladding material replacing silicon carbide (SiC) in nuclear fuel kernel. As cladding material, hafnium content in zirconium must be below 0.01% or 100 ppm. This because hafnium has neutron capture cross section 470 higher than zirconium. This property of hafnium will disturb the fission nuclear reaction. Beside that hafnium can be used as controlling rod materials so the separation of these two materials is very important. However, zirconium and hafnium are very difficult to separate due to similarity in their chemical properties and ionic radii. Separation method based on differences in adsorption properties has been applied such as continuous annular chromatography (CAC) using cation resin. The separation effectiveness strongly depends on diffusivity and adsorption affinity of components in the bed of resin. In this work, adsorption constant of components in Dowex 1 X8 anion resin were determined by using batch experiment. Beside that the diffusivities of each component through the resin bed also determined in this work. The separation of zirconium and hafnium using annular chromatography was simulated. The effect of feed and eluent flowrate, rotation speed and height of resin on CAC resolution was studied in order to suggest the optimum condition for separation process. Three different isotherm equilibrium models were proposed in order to fit the equilibrium experimental data. Simulation showed that distribution equilibrium model could fit the experimental data very well. The distribution coefficient for zirconium and hafnium were 6.16x10-3dm3/g resin and 4.72x10-3dm3 /g resin respectively. A column glass resin was used to determine the diffusivities of zirconium and hafnium. Two mathematical models were proposed such as rate-based model (RBM) and equilibrium-based model (EBM) to fit the experimental data. Simulation result showed that the RBM could fit the experimental data better than EBM. The diffusivities of zirconium and hafnium were 8.78x10-5cm2/s and 7.32x10-5cm2/s respectively. Meanwhile the overall mass transfer coefficient of zirconium and hafnium were 2.35x10-21/s and1.11x10-21/s respectively. The simulation result of separation zirconium and hafnium using CAC based on equilibrium model showed that zirconium and hafnium could be separated using CAC with diameter 20 cm and 20 cm of resin height. The feed and eluent flowrate was 0.03 cm/s and the rotation speed was 0.209 rpm.